Encounter between the Prophet’s Sunna and the Society Tradition: a Study of Living Sunna in Puncu Sub-District, Kediri District - Anam, Wahidul (ADDIN, 2020)
Sunna, the prophet Muhammad’s traditions and practices, always develop and come to the attention of the next generation of Muslims. Indonesian Muslims as followers of the largest Islamic religion in the world have a unique concept in terms of the struggle of tradition from the relics of local religions with the teachings of Islam. The dialectics proceed dynamically as developed by Walisanga (the nine revered saints of Islam in Indonesia), which was known later as the cultural and religious acculturation model. This paper will describe how the process of religious acculturation with local culture in Puncu Sub-District, Kediri can be implemented well, especially related to their practice in carrying out the traditions of the Prophet Muhammad in their various religious lives. Some fundamental questions to be answered are how the process and form of living Sunna as well as the factors that influence the acculturation process applied in these. For this reason, this type of research is interdisciplinary, by not only based on the science of hadith, but also using an anthropological approach and cultural acculturation theory. The results found include: (1) traditions practiced in Puncu such as rituals in the process of birth, marriage, and body management are forms of living Sunna that have become customs and become part of the acculturation of local religion and culture that is going well; (2) this can be realized with at least a number of factors, including: the role of religious scholars and religious leaders with moderate characters, government officials who care about diversity, the existence of religious institutions that contribute to the cultivation of acculturation so as to minimize conflicts between local religions and cultures, as well smooth the agenda of faith and community traditions simultaneously.